If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -16) = 48 + -1(7x + 62) Reorder the terms: 2(-16 + x) = 48 + -1(7x + 62) (-16 * 2 + x * 2) = 48 + -1(7x + 62) (-32 + 2x) = 48 + -1(7x + 62) Reorder the terms: -32 + 2x = 48 + -1(62 + 7x) -32 + 2x = 48 + (62 * -1 + 7x * -1) -32 + 2x = 48 + (-62 + -7x) Combine like terms: 48 + -62 = -14 -32 + 2x = -14 + -7x Solving -32 + 2x = -14 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. -32 + 2x + 7x = -14 + -7x + 7x Combine like terms: 2x + 7x = 9x -32 + 9x = -14 + -7x + 7x Combine like terms: -7x + 7x = 0 -32 + 9x = -14 + 0 -32 + 9x = -14 Add '32' to each side of the equation. -32 + 32 + 9x = -14 + 32 Combine like terms: -32 + 32 = 0 0 + 9x = -14 + 32 9x = -14 + 32 Combine like terms: -14 + 32 = 18 9x = 18 Divide each side by '9'. x = 2 Simplifying x = 2
| 8x-3=-3+4x | | 2n-29=-25+4n | | 9c-13-6c+10= | | 3x+4(0)=-12 | | 9x-4(x+5)=8(x+3)+1 | | x-y+z=1 | | 2(0)+y=4 | | 6(3+2x)-4=50 | | 3x^2-12y=0 | | 14n+8=-50 | | 4x=2+8x-10x+18 | | 5(5x-2)=65 | | x+9y=31 | | -9m-4=12 | | 25=1-3d | | .3b-8.4=1.5b | | x+4-3=9 | | 6=-7x-8 | | 4c-1.4=0.6 | | 0.8x-2.8=0.4 | | 5x+3=28 | | y=.25(-4)-2 | | 10+8y=16y | | 1-6x-4x=12 | | 2(a-4)+3(a+2)=3 | | (6*y)*3=6*(y*3) | | 2(a-4)+3(a+2)=16 | | 9d+sd+3d-4=5d | | 7x-8y=3 | | 17=t+8 | | 3x+5=12-y | | 4p+25=6(p-3)-3(4-3p) |